2018
DOI: 10.1021/acs.jpcc.8b08041
|View full text |Cite
|
Sign up to set email alerts
|

Anion-dependent Hot Carrier Dynamics in Chalcogenide Perovskites SrSnX3 (X = S, Se)

Abstract: The hot carrier relaxation dynamics in inorganic perovskites SrSnS3 and SrSnSe3 has been investigated using nonadiabatic molecular dynamics simulation. The results indicate that the hot carrier relaxation dynamics strongly depends on the chalcogenide element. It is found that the hot electrons and hot holes have a fast relaxation time in SrSnS3 than SrSnSe3 with the similar excess energy due to the strong nonadiabatic couplings. Moreover, the hot holes hold a dramatic faster decay time than hot electrons for b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…[ 174 ] Guo and Wang analyzed hot carrier dynamics in SrSnX 3 (X = S,Se) and concluded that the decay times are longer than in organic–inorganic perovskites. [ 175 ] Unfortunately, as concluded in Section 2, these compounds are unlikely to form. Whether more stable chalcogenide perovskites exhibit similarly favorable hot carrier dynamics remains to be determined.…”
Section: Optoelectronic Properties and Defect Chemistrymentioning
confidence: 99%
“…[ 174 ] Guo and Wang analyzed hot carrier dynamics in SrSnX 3 (X = S,Se) and concluded that the decay times are longer than in organic–inorganic perovskites. [ 175 ] Unfortunately, as concluded in Section 2, these compounds are unlikely to form. Whether more stable chalcogenide perovskites exhibit similarly favorable hot carrier dynamics remains to be determined.…”
Section: Optoelectronic Properties and Defect Chemistrymentioning
confidence: 99%
“…To understand the relaxation process better, the averaged carrier-phonon NAC in Cs 2 TiI y Br 6Ày was calculated. 22,24,45 The formula for the average carrier-phonon NAC is…”
Section: Resultsmentioning
confidence: 99%
“…[46][47][48] The inuence spectrum is the Fourier transformation (FT) of the energy gap uctuation between the related transition and it represents the vibration modes that relate to the carrier relaxation process. 22,49 The obtained inuence spectrum for the relaxation processes of hot carriers for Cs 2 TiI y Br 6Ày are presented in Fig. 6.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations